Safety and Feasibility of Single-incision Laparoscopic Distal Pancreatectomy. Issue 4 (18th August 2022) - Sasaki, Toshihide; Yang, Ching-Yao; Nakagawa, Kenji; Nagai, Minako; Nishiwada, Satoshi; Terai, Taichi; Sho, Masayuki
Abstract : Background: Comparative studies regarding single-incision laparoscopic distal pancreatectomy (SILS-DP) are limited. This study aimed to compare the short-term outcomes of SILS-DP with conventional laparoscopic DP (C-LDP) under strict indication criteria. Materials and Methods: We retrospectively reviewed the patient characteristics and surgical outcomes of those who underwent either SILS-DP or C-LDP at National Taiwan University (NTU) and C-LDP at Nara Medical University (NMU) between 2009 and 2019. SILS-DP was indicated for benign or low-grade malignant pancreatic tail tumors and was performed along with splenectomy. Results: We compared 12 cases of SILS-DP with 31 of C-LDP from NTU and 17 of C-LDP from NMU. Patients in the SILS-DP group had significantly less blood loss than the C-LDP group at NTU ( P =0.028). Postoperative outcomes, including the postoperative hospital stay and clinically relevant pancreatic fistula, were not significantly different between the 2 groups. Although SILS-DP was performed by a surgeon who was well-experienced with laparoscopic surgeries, the first few cases had a larger amount of blood loss, longer operation time, and a higher rate of complications. Such unfavorable outcomes were likely to be resolved shortly. No reoperations and deaths were noted. Conclusion: SILS-DP is feasible when performed by an experienced surgeon and in carefully selected patients.